KONSTRUKSI KARAKTER SISWA VIA PEMBIASAAN SHALAT DHUHA - Atika Andayani; Zaini Dahlan (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
Research was conducted to provide a description of the character construction of students through the habituation of dhuha prayers at MIS Terpadu Mutiara Hikmah Hessa Perlompongan. The research was conducted using qualitative methods conducted. The collection of information and data was carried out by interviewing techniques with Mr. Suyanto, S.Ag as the Head of Madrasah as the main source, Mrs. Martiya as the guardian of class 6-A, Mrs. Nisa as the 2-A class guardian and also Mrs. Wati as the office staff. Then observation and documentation is taken where the student is the subject. The data analysis technique used goes through three stages: data reduction, data display and drawing conclusions. The validity of the data is tested through engineering triangulation and source triangulation. The results of the research obtained that through the habituation of dhuha prayer at MIS Terpadu Mutiara Hikmah, there are five characters formed in students, namely: (1) Religious; (2) Discipline; (3) On Time; (4) Responsibility; And (5) Honestly. The character of discipline becomes the most prominent character because students are able to manage the time when taking wudhu, preparing prayer equipment to order themselves so that they can perform dhuha prayers immediately and do not interfere with study time later. While on the character of responsibility is shown by the class leader and the imam of prayer. As the leader, the class leader directs his friends not to pray, and as an imam order the shaf and ensure the safe and orderly running of dhuha prayers.